موقف الفقه الإسلامي من العنف ضد الزوجات في مملكة البحرين = The position of Islamic jurisprudence on violence against women in the Kingdom of Bahrain - Abdraboh Abdullah, Salman Mohsen; Sitiris, Miszairi (IIUM Press, 2019)
The phenomenon of violence in the Kingdom of Bahrain in the year 2004 was recorded on the number of (620) subjected to women of Bahrain and (178) wives were subjected to violence by their husbands and this is a large percentage that we cannot be ignored, due to the following reasons: weak legal culture, lack of awareness of Islamic teachings, misunderstanding of guardianship, masculinity and violence, absence of deterrent, tribal culture, drug abuse and alcohol abuse. Social pressures, education theory, lack of self-esteem, women’s lack of awareness of their rights. The attempt to preserve the family structure, lack of financial resources for women, access to higher education for men, incompetence, and inferiority of women in society.The researchers followed the descriptive approach. The researchers relied on the analytical descriptive method by studying the phenomena on the ground, describing them accurately without exaggerating them, and analyzing issues related to the domestic violence in the Kingdom of Bahrain.